PENDAMPINGAN USAHA DUPA BAGI KELOMPOK MASYARAKAT DISABILITAS DI DESA BENGKALA, BULELENG, BALI - I Ketut Sida Arsa; I Wayan Karyasa; Ni Made Ary Widiastini (Universitas Sebelas Maret, 2019)
Bengkala Village in Buleleng Regency has been known as an area that is home to people with a hearing impairment. Their inability to communicate verbally like people in general does not make a group of people with disabilities unable to work. In this community service activity, people with disabilities in Bengkala Village are given training and guidance to produce incense that can be sold to people around and outside the village. Incense as a daily necessity product for the Balinese Hindu community, is a prospective business opportunity to be developed. Understanding the limitations of the people with disabilities, the accompanying method provided is the plasma system. As adopted Law No. 9 of 1995, this assistance was provided with an understanding of the conditions of the community, that's why, the directive approach is applied to community service activities. In its application, a directive approach is applied by adopting a plasma core pattern. Through the plasma method, the community is given technical guidance on production to be able to produce the expected number of products, both quality and quantity, it is about 20 kilograms per day.Key words: Bengkala Village, business, disability, group, insence